Effects of heparin and aminoguanidine on anaphylatoxin activity in the guinea-pig - Sackeyfio, A.C.; Hicks, R (European Journal of Pharmacology, 1987)
Heparin inhibited the bronchoconstrictor and pressor responses to histamine and anaphylatoxin. However, anaphylatoxin-induced hypotension, in contrast to that induced by histamine, was resistant to heparin inhibition. Aminoguanidine alone had no effect upon histamine or anaphylatoxin but it abolished the heparin-induced inhibition. It is therefore concluded that histamine mediates the bronchiolar and pressor but not the hypotensive effects of anaphylatoxin. Furthermore, anaphylatoxin causes the release of heparin to modulate the bronchiolar effects of extra-pulmonary histamine